Neotropical ant-plant Triplaris americana attracts Pseudomyrmex mordax ant queens during seedling stages (2017)
The association between the myrmecophyte Triplaris and ants of the genus Pseudomyrmex is an often-reported example of mutualism in the Neotropics. The ants colonize the hollow stems of their hosts, and in exchange, the plants benefit from a reduced degree of herbivory. The previous studies have shown that workers can discriminate their host from other plants, including a closely related species. Little is known about how queens locate their host during the colonization process, but it has been suggested that host recognition is mediated by volatiles. Since queens of Pseudomyrmex mordax colonize their hosts during the seedling stage, we hypothesized that queens would discriminate leaves of seedlings from adult plants. To evaluate our hypothesis, we used a two-sided olfactometer, to test the preference of queens towards different leaf and plant ages of Triplaris americana. Virgin queens of Pseudomyrmex mordax preferred seedlings over adult plants, as well as plant leaves over empty controls, showing no discrimination for leaf age. Our results suggest that the volatiles virgin queens recognize are either produced or are more abundant at the early growing stage of the host when colonization is crucial for the host's survival. © 2017, The Author(s).